The Effect of Different Head Movement Paradigms on Vestibulo-Ocular Reflex Gain and Saccadic Eye Responses in the Suppression Head Impulse Test in Healthy Adult Volunteers - Starkov, Dmitrii; Vermorken, Bernd; Van Dooren, T. S.; Van Stiphout, Lisa; Janssen, Miranda; Pleshkov, Maksim; Guinand, Nils; Pérez Fornos, Angelica; Van Rompaey, Vincent; Kingma, Herman; Van de Berg, Raymond (Frontiers in Neurology, 2021)
Objective: This study aimed to identify differences in vestibulo-ocular reflex gain (VOR gain) and saccadic response in the suppression head impulse paradigm (SHIMP) between predictable and less predictable head movements, in a group of healthy subjects. It was hypothesized that higher prediction could lead to a lower VOR gain, a shorter saccadic latency, and higher grouping of saccades. Methods: Sixty-two healthy subjects were tested using the video head impulse test and SHIMPs in four conditions: active and passive head movements for both inward and outward directions. VOR gain, latency of the first saccade, and the level of saccade grouping (PR-score) were compared among conditions. Inward and active head movements were considered to be more predictable than outward and passive head movements. Results: After validation, results of 57 tested subjects were analyzed. Mean VOR gain was significantly lower for inward passive compared with outward passive head impulses (p < 0.001), and it was higher for active compared with passive head impulses (both inward and outward) (p ≤ 0.024). Mean latency of the first saccade was significantly shorter for inward active compared with inward passive (p ≤ 0.001) and for inward passive compared with outward passive head impulses (p = 0.012). Mean PR-score was only significantly higher in active outward than in active inward head impulses (p = 0.004). Conclusion: For SHIMP, a higher predictability in head movements lowered gain only in passive impulses and shortened latencies of compensatory saccades overall. For active impulses, gain calculation was affected by short-latency compensatory saccades, hindering reliable comparison with gains of passive impulses. Predictability did not substantially influence grouping of compensatory saccades.